2021
DOI: 10.3390/molecules26071858
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Proteolytic Enzymes Produced by Lactic Acid Bacteria

Abstract: Over the past several decades, we have observed a very rapid development in the biotechnological use of lactic acid bacteria (LAB) in various branches of the food industry. All such areas of activity of these bacteria are very important and promise enormous economic and industrial successes. LAB are a numerous group of microorganisms that have the ability to ferment sugars into lactic acid and to produce proteolytic enzymes. LAB proteolytic enzymes play an important role in supplying cells with the nitrogen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(105 citation statements)
references
References 124 publications
2
101
0
2
Order By: Relevance
“…This phenomenon is explained by the low protein content of the pineapple by-products used as a carbon source for the preparation of the fermentation broth [ 8 ]. Indeed, to ensure good growth of the lactic ferment and consequent production of LA, the production medium must contain a sufficient quantity of protein to meet the nitrogen requirements of the fermenting strain [ 26 ]. Moreover, this LA production was improved when the different production media were supplemented with BC, BF, and BBIP; these by-products would therefore be potential sources of amino acids and peptides that served as a nitrogen source for the lactic ferment.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is explained by the low protein content of the pineapple by-products used as a carbon source for the preparation of the fermentation broth [ 8 ]. Indeed, to ensure good growth of the lactic ferment and consequent production of LA, the production medium must contain a sufficient quantity of protein to meet the nitrogen requirements of the fermenting strain [ 26 ]. Moreover, this LA production was improved when the different production media were supplemented with BC, BF, and BBIP; these by-products would therefore be potential sources of amino acids and peptides that served as a nitrogen source for the lactic ferment.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the supply of these essential nutrients, LAB possess proteolytic enzymes, bound to their cell walls, which degrade the proteins in the substrate, accumulating peptides and free amino acids. Some of the released peptides have been demonstrated to possess important bioactivities in the host [54]. In their fermentative processes, LAB-the main group of bacteria used for food and feed fermentations-release a number of bioactive metabolites, such as biogenic amines, exopolysaccharides, bacteriocins, and other biologically active, proteolytically released peptides [50][51][52].…”
Section: Lab Applications In Animal Productsmentioning
confidence: 99%
“…To ensure the supply of these essential nutrients, LAB possess proteolytic enzymes, bound to their cell walls, which degrade the proteins in the substrate, accumulating peptides and free amino acids. Some of the released peptides have been demonstrated to possess important bioactivities in the host [ 54 ]. For instance, bacteriocinogenic strains of LAB can be added to foods as starter cultures, co-cultures, or bioprotective cultures, to improve food quality and safety, as reported in fermented meat and cheese [ 55 , 56 ].…”
Section: Lab Applications In Animal Productsmentioning
confidence: 99%
“…A previous study has indicated a positive correlation between the glucose dehydrogenase (GDH) activity in lactic acid bacteria and their ability to metabolize amino acids. Co-metabolism of citric acid and glutamate can result in higher amino acid conversion rates [44]. Finally, organic acids can improve the oxidation resistance of sourdough.…”
Section: Tca-cycle Of MIX Sourdoughmentioning
confidence: 99%